1988
DOI: 10.1136/gut.29.2.206
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer in ulcerative colitis: a cohort study of primary referrals from three centres.

Abstract: SUMMARY A retrospective cohort of 823 patients with ulcerative colitis who resided at the time of diagnosis in one of three defined geographical areas (West Midlands region, Oxford region, England and Stockholm County, Sweden) was assembled. The patients were first seen at named hospitals in these areas and the diagnosis of ulcerative colitis established within five years of onset of symptoms between 1945-1965. All patients were 15 years of age or more at onset of disease and were followed for a minimum of 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
183
1
13

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 460 publications
(201 citation statements)
references
References 24 publications
4
183
1
13
Order By: Relevance
“…3). 3 Differences from all other experimental groups were statistically significant (p < 0.02).- 4 Differences from WT mice with AOM or AOM1TNBS were statistically significant (p<0.02).- 5 Difference from IL-4 2/2 mice treated AOM was statistically significant (p < 0.02). …”
Section: Immunohistochemistrymentioning
confidence: 79%
See 1 more Smart Citation
“…3). 3 Differences from all other experimental groups were statistically significant (p < 0.02).- 4 Differences from WT mice with AOM or AOM1TNBS were statistically significant (p<0.02).- 5 Difference from IL-4 2/2 mice treated AOM was statistically significant (p < 0.02). …”
Section: Immunohistochemistrymentioning
confidence: 79%
“…1 Of note, patients with longstanding, extensive UC have a high cancer risk,~16.5% at 30 years, after initial diagnosis. 2,3 It has long been noted that cancer arises from regions of chronic inflammation, and the inflammatory cells and cytokines of the immune system found in tumors are more likely to contribute to tumor growth and progression. 4 In animal models, colitis induced by dextran sulfate sodium (DSS) are associated with dysplasia and cancer.…”
mentioning
confidence: 99%
“…The lumenal concentration of TNFa is increased in patients with in¯ammatory bowel disease (Braegger et al, 1992), a condition which predisposes to colorectal cancer (Gyde et al, 1998). Fecapentaene-12, the most abundant form of a group of mutagenic chemicals found in the faeces of individuals who consume a Western diet high in fat and meat (Schi man et al, 1989), has been shown to be a tumour promotor in a rat model of colorectal cancer (Zarcovic et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that IBD patients with proctitis and proctosigmoiditis are at the lowest risk of CACRC and the higher risk is combined with left-sided colitis and pan-colitis [15,16].…”
Section: Risk Factors In Cacrcmentioning
confidence: 99%